PELANGGARAN KESANTUNAN BERBAHASA BUPATI DI SUMATERA BARAT DI DALAM MEDIA SOSIAL - Putra, Riyan Nofardo; Juita, Novia; Ngusman, Ngusman (Universitas Negeri Padang, 2018)
AbstractThe purpose of this research to describe violations of the principles of linguistic politeness regent in West Sumatera in the social media. This study uses qualitative research in descriptive form. The data of this research was social media regent in West Sumatera Barat, especially Facebook. The steps used in the form of screenshoting, transcribing, observing, and clasificating the data include in the violation of linguistic politeness. The analysis of data is done through classifying data, analyzing data, interpreting data, and drawing conclusions. The result of data analysis show that from 450 sentence of regent in West Sumatera, found the use principle of linguistic politeness as 439 sentences and who violated as 11 sentences. Based on the results of the data can be concluded the speech regent in West Sumatera in social media categorized polite.Keywords: linguistic politeness, regent, social media